Pengaruh Model Pembelajaran Quantum Berbantuan Media Tiga Dimensi Terhadap Hasil Belajar IPA - Winda, Ni Komang; Dibia, I Ketut; Sudarma, I K (Universitas Pendidikan Ganesha, 2018)
This research aimed at finding out the significant difference of science learning outcomes among the group of students who were taught by Quantum learning model aided three dimensional media and the group of students who were taught by conventional learning model on fifth grade students at Cluster I Sukasada Sub-district, Buleleng Regency in Academic Year 2017/2018. This research was a quasi-experimental research with the non-equivalent post-test only control group design. The population of this research was the entire fifth grade students at Cluster I Sukasada Sub-district, Buleleng Regency in Academic Year 2017/2018 which amounted to 175 people. The sample of this research was fifth grade students of SD Negeri 2 Wanagiri which was selected as the experimental group and fifth grade students of SD Negeri 2 Wanagiri which was selected as the control group. The obtained data were analyzed by using descriptive statistical analysis and inferential statistical analysis. The result of this research showed there was a significant difference of science learning outcomes among the group of students who were taught by Quantum learning model-aided three-dimensional media and the group of students who were taught by conventional learning model on fifth grade students at Cluster I Sukasada Sub-district, Buleleng Regency in Academic Year 2017/2018. Therefore, it can be concluded that Quantum learning model aided three dimensional media has a positive effect on fifth grade students’ learning outcomes at Cluster I Sukasada Sub-district Buleleng Regency in Academic Year 2017/2018